Carbonization of Refuse-Derived Fuel Pellets with Biomass Incorporation to Solid Fuel Production - Andrei Longo; Nuno Pacheco; Roberta Panizio; Cândida Vilarinho; Paulo Brito; Margarida Gonçalves (Fuels)
In this work, dry carbonization (DC) and hydrothermal carbonization (HTC) of refuse-derived fuel (RDF) pellets were conducted to evaluate the physical, chemical, and fuel properties of the produced chars. In the dry carbonization tests, biomass sawdust was incorporated in different proportions on the samples to minimize agglomeration caused by the melting of the plastic fraction. The experiments were carried out in a temperature of 400 °C (DC) and 250–300 °C (HTC), in a residence time of 30 min. The respective chars and hydrochars were characterized according to their mass yield, apparent density, proximate, elemental, and mineral composition, chlorine content, high heating value, thermogravimetric profile, and surface functional groups. The results showed that the dry carbonization of RDF pellets with biomass incorporation, followed by a washing step, resulted in the production of chars with improved properties such as higher fixed carbon and higher heating value (HHV) (25–26 MJ/kg) and lower ash and chlorine content. Additionally, the HTC experiments demonstrated that hydrochars showed improved properties without the need for biomass addition and washing, however, with no significant difference in the HHV (20–21 MJ/kg). Therefore, DC of RDF pellets with 10% biomass incorporation seems to be a promising option to overcome the constraints of RDF utilization as an alternative fuel.